PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL GAME BASED LEARNING BERBANTUAN QUIZIZZ - Aziz Arzaqi Jannata; Andrizal Andrizal; Hasan Maksum; Toto Sugiarto (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Student engagement plays a crucial role in supporting successful learning outcomes, particularly in vocational education settings. Initial classroom observations conducted in Class XI TKR of SMK Negeri 1 Kecamatan Luak indicated that learners tended to show limited participation during instructional activities. This classroom action research investigated the use of a game-oriented learning approach supported by Quizizz to foster greater student involvement in the Light Vehicle Engine System subject. The study followed the Kemmis and McTaggart action research framework and was carried out in two cycles, each consisting of two learning sessions. Twenty-six students participated in the research. Data were obtained through systematic classroom observations and interpreted using percentage-based descriptive analysis. Findings revealed a steady rise in learner engagement throughout the intervention. Participation levels progressed from 34.61% during the first session of Cycle I to 46.15% in the following session, increased again to 65.38% at the beginning of Cycle II, and reached 80.76% by the final meeting. These outcomes surpassed the predetermined criterion requiring at least 75% of learners to demonstrate moderate, high, or very high engagement. The results suggest that integrating Quizizz within a game-oriented instructional model can effectively encourage active participation in vocational learning environments.Keywords: Game Based Learning, Quizizz, Student Learning Activity, Classroom Action Research, Light Vehicle Engine System